“Crisscross” Approach: An Unconventional Technique for Simultaneous Antegrade and Retrograde Catheterization through Femoral Access - Siju T Abraham; Vishnu Motukuru; Vivek Anand; KB Sumanth Raj (Indian Journal of Vascular and Endovascular Surgery)
Background: Contralateral retrograde femoral (crossover) approach is the preferred modality for revascularization of iliac, femoral, popliteal, and tibial vessel in patients with chronic limb-threatening ischemia (CLTI). This approach, however, can be demanding in patients with tortuous iliac arteries, distal aortic calcification, and scarred contralateral groin. Flip techniques have been successfully deployed as an alternative to crossover approach to deal with concomitant iliac artery and infrainguinal lesions. Nevertheless, flip techniques have also been associated with complications such as loss of access and dissection at access site. We describe a unique “crisscross” technique which involves concurrent use of retrograde and antegrade sheaths through femoral access for the treatment of ipsilateral iliac and infrainguinal lesions with focus on procedural outcomes and complications. Materials and Methods: This is a case series of 22 patients who underwent percutaneous “crisscross” access for recanalization of lower limb lesions between January 2020 and April 2024. Outcomes were measured included technical and hemodynamic success, and access related complications such as hematoma, bleeding, and pseudoaneurysm formation. Results: Of the 22 cases, retrograde common femoral artery access using 7 Fr sheath was obtained in 15 (68.2%) patients for recanalization of iliac lesion (2 patients had conversion from diagnostic 5 Fr to therapeutic 7 Fr sheath). In the remaining 7 (31.8%) patients, 5 Fr retrograde sheath was utilized for diagnostic iliac artery digital subtraction angiogram due to inconclusive preoperative clinical and radiological findings. All 22 (100%) patients underwent successful infrainguinal revascularization using 6 Fr antegrade sheath across the proximal superficial femoral artery. Technical and hemodynamic success was achieved in all 22 patients. Only 2 (9.1%) patients developed mild hematoma at the access site with no major access related complications. Conclusion: “Crisscross” technique can be considered a safe and effective approach for revascularization of ipsilateral concomitant iliac artery and infrainguinal lesions in patients with CLTI.